Optimizing the Risk Assessment in Upper Gastrointestinal Bleeding: Comparison of 5 Scores Predicting 7 Outcomes - Cúrdia Gonçalves, Tiago (2018)
Although different scores have been suggested to predict outcomes in the setting of upper gastrointestinal bleeding (UGIB), few comparative studies between simplified versions of older scores and recent scores have been published. We aimed to evaluate the accuracy of pre- (PreRS) and postendoscopic Rockall scores (PostRS), the Glasgow-Blatchford score (GBS) and its simplified version (sGBS), as well as the AIMS65 score in predicting different clinical outcomes.